Leiomyosarcoma Of Urinary Bladder - Akole, Raghvendra; Bhambani, Pawan; Nema, S. K.; Singh, Arjun (Asian Journal of Medical Research, 2013)
Mesenchymal tumours represent a small number of bladder malignancies. Leiomyosarcoma is the most common histological variant with 0.1% of bladder cancer. This tumour has been historically considered as highly aggressive and shows a poor prognosis. Despite very low survival rates showed in older reports, some authors indicate that some patients could have a better outcome. Immunohistochemical studies play an important role in the diagnosis of this tumour. Wide surgical excision with adjuvant chemotherapy is the mainstay of treatment. We report a case of 50 year old female presented with high grade leiomyosarcoma of urinary bladder.